Awareness of Surgical Cost in Gynecology [09B]. (May 2020) - Menzies, Anya V.; Cochrane, Elizabeth; Kim, Sara; Dayton, Samantha; Chappelle, Joseph; Burke, William
Abstract : INTRODUCTION: With the rising cost of healthcare in the United States, recent efforts have focused on reducing healthcare spending without compromising quality and outcomes. Studies have suggested that most surgeons are unaware of the costs related to surgery. The purpose of our study was to assess provider knowledge of the cost of surgical instruments and adjuncts used during gynecologic laparoscopy. METHODS: After IRB approval was obtained, an anonymous survey of practicing gynecologists, OR technologists, and OR nurses at Stony Brook University Hospital was conducted. We inquired about duration of training, formal education regarding cost, self-awareness of cost, and cost estimates for 37 commonly used disposable surgical instruments and items. Similarly to previously published studies assessing cost in other surgical specialties, we defined cost estimate accuracy as within 20% of the hospital cost. RESULTS: A total of 104 surveys were distributed, and 29 complete responses (28%) were received. Of the participants, 17 were attendings, 3 were fellows, 6 were residents, and 3 were OR techs and nurses. On average, participant estimates were within the defined accuracy range for only 13.5% items. There were no differences in accuracy when comparing educational level, years in practice, self-perceived awareness, history of formal cost education, or whether individuals factor in cost. CONCLUSION: Gynecologic surgeons and trainees have poor awareness regarding the cost of the items used during laparoscopic surgery. Providing further education regarding the cost of these items may aid surgeons in making more informed choices and help reduce healthcare costs.